HUBUNGAN INTENSITAS MENONTON TAYANGAN KEKERASAN DI TELEVISI DENGAN PERILAKU AGRESIF YANG DILAKUKAN ANAK USIA SEKOLAH DI MADRASAH DINIYAH AWALIYAH NURUL HUDA PAJAR BULAN - Riski Amelia; Ruri Fitriyani (Psikis : Jurnal Psikologi Islami, 2016)
This  study  purpose  to  determine  the  relationship  of  the  intensity  of  watching  violence  on television with aggressive behavior in school-aged children in Madrasah Diniyah Awaliyah Nurul Huda  Pajar  Bulan.  The  hyphotesis  proposed  in  this  research  is  there  is  correlation  between intensity  of  watching  violence  on  television  with  aggressive  behavior  in  school-aged  children  in Madrasah  Diniyah  Awaliyah  Nurul  Huda  Pajar  Bulan.  The  higher  the  aggressive  behavior,  and vice versa the lower the intensity of watching violence on television, the lower aggressive behavior. Of subjects used in this study were 70 students/grade III and IV Madrasah Diniyah  Nurul Huda Pajar Bulan aged 10-12 years. Data collection using two kinds of scale, the scale of the intensity of watching violence on the television and aggressive behavior scale. Data anayisis methods used in the  study  is  the  simple  regression  analysis.  All  caunting  data  analysis  was  performed  using  the computer  program  SPSS  version  17.  The  resuld  of  the  analysis  obtained  corellation  coefisien  of R=0,807, P=0,000 means that the hypothesis is accepted